2021
DOI: 10.1002/mnfr.202100153
|View full text |Cite
|
Sign up to set email alerts
|

Copper‐Binding Peptides Attenuate Microglia Inflammation through Suppression of NF‐kB Pathway

Abstract: Scope: Activation of microglia, the resident immune cells of the central nervous system, has been related to the etiology and progression of neurodegenerative diseases; thus, finding novel approaches to suppress the neuroinflammatory process is of utmost relevance. Methods and Results: The anti-inflammatory activity of whey Cu-, Fe-, and Zn-binding peptides and their possible underlying mechanism of action were evaluated in microglia. Whey metal-binding peptides decreased nitric oxide production and tumor necr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 49 publications
(64 reference statements)
0
6
0
Order By: Relevance
“…[ 40 ] Copper-binding peptides have also been shown to attenuate microglia inflammation by suppressing the NF-kB pathway field. [ 41 ] Consequently, the anti-inflammatory activity of copper is becoming a research hotspot.…”
Section: Discussionmentioning
confidence: 99%
“…[ 40 ] Copper-binding peptides have also been shown to attenuate microglia inflammation by suppressing the NF-kB pathway field. [ 41 ] Consequently, the anti-inflammatory activity of copper is becoming a research hotspot.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that Cu-binding peptide (Cu-bp) inhibits the translocation of NF-κB p65 to the nucleus to alleviate the inflammatory response of microglia. [ 59 ] Accumulation of copper in cells leads to disrupted mitochondrial autophagy and overexpression of the NLRP3/caspase-1/GSDMD protein axis in microglia. Copper also activates the secretion of NO, TNF-α and IL-6 by M1-type microglia.…”
Section: Mechanisms By Which Copper Overload Affects Cognitive Functionmentioning
confidence: 99%
“…Numerous studies have found that proinflammatory microglia-mediated neurotoxicity in neurodegenerative diseases largely depends on the activation of the NF-κB pathway. Inhibition of NF-κB signaling selectively in microglia by chemicals can alleviate the production of pro-inflammation cytokines, chemokines, ROS, and nitric oxide, suppress LPS and other inflammatory trigger-induced microglial activation and attenuate microglia-mediated neuronal damage [ 20 , 21 , 22 ]. In a mouse model of ALS, NF-κB DNA-binding activity is predominately increased in microglia with disease progression.…”
Section: Nf-κb Pathway Is Essential For Microglial Activation and Sub...mentioning
confidence: 99%